Increase in Gamma Band qEEG Activity during Executive Coaching: Some Preliminary Observations and Possible Implications - Lyra Puspa; Nurhadi Ibrahim; Paul T. Brown (Fakultas Ilmu Pendidikan)
Executive coaching has become a well-established method of leadership development in many organizations. However, nothing is known about what effects coaching processes have on brain activity in understanding the neurobiological basis of behavioral changes. Using quantified electroencephalogram (qEEG) activity in the gamma-band range, this pilot study is the first attempt to elucidate the electro-cortical patterns that are induced during an executive coaching process whilst using a specific intervention called the CARE Model. Gamma-band oscillation has been related to gestalt perception, the state of consciousness, and cognitive functions. Synchronization of gamma-band has also been proposed as being involved in the mechanisms of functional integration underlying changes in neural circuitry. Despite the decades of gamma-band studies, the possibility that executive coaching might induce gamma-band oscillations has not yet been explored. The subjects were six top talent volunteers (male, mean age = 30). The EEG was recorded from 19 electrodes of the International 10/20 System in both the resting state as the baseline and the continuous 45-minute coaching session. Logarithmically transformed absolute spectral power values of gamma-band were calculated for 3s epochs; and a 182 epochs comparison of each CARE Model stage with the baseline was analyzed using Wilcoxon signed-rank test. Our preliminary qEEG observations show that gamma-band activity became significantly increased in the frontal and posterior regions of the subjects during the coaching process. These preliminary results suggest that the neural impact of executive coaching within the CARE Model may be to evoke a self-reflecting process, gestalt perception, and associative learning.